2023
DOI: 10.1002/ctm2.1509
|View full text |Cite
|
Sign up to set email alerts
|

USP7 promotes non‐small‐cell lung cancer cell glycolysis and survival by stabilizing and activating c‐Abl

Yuanming He,
Shuoyi Jiang,
Yueya Zhong
et al.

Abstract: BackgroundAbelson tyrosine kinase (c‐Abl) is frequently mutated and highly expressed, and promotes non‐small‐cell lung cancer (NSCLC) survival, metastasis and tumorigenesis. c‐Abl could also be modified through ubiquitination, but the underlying mechanism is not well understood.MethodsMass spectrometry assays were performed to search c‐Abl deubiquitination enzymes. The molecular mechanism was determined using Co‐IP assays, pull‐down assays, Western blotting upon gene knockdown or overexpression. Cell lines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…USP7 is a member of the ubiquitin-specific protease family and can scavenge the ubiquitin modification of the substrate, thereby protecting the substrate from proteolysis [ 42 , 68 ]. Previous studies have shown that USP7 plays different roles in the development of cancer [ 69 ]. A recent study showed that high USP7 expression was associated with poor survival and later tumor stage in GBM [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…USP7 is a member of the ubiquitin-specific protease family and can scavenge the ubiquitin modification of the substrate, thereby protecting the substrate from proteolysis [ 42 , 68 ]. Previous studies have shown that USP7 plays different roles in the development of cancer [ 69 ]. A recent study showed that high USP7 expression was associated with poor survival and later tumor stage in GBM [ 70 ].…”
Section: Discussionmentioning
confidence: 99%